Perancangan Perangkat Lunak Pengembangan Motif Kreasi Dari Motif Batik Kalimantan Barat Menggunakan Operasi Geometri Pada Pengolahan Citra - Monalisa, Tatum Tristy (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
Batik is one of the heritagesin Indonesia that needs to be remained anddeveloped. There are several types andpatterns in traditional Batik that suit to thephilosophies and the customs of each region inIndonesia. One of the Batik varieties in Indonesia is based on the custom in WestBorneo. However, it takes a long time to thebatik designers in West Borneo in creatingnew batik patterns. This research is aimed to create asoftware in resulting new varieties in Batikpatterns of West Borneo. Through thissoftware (BAKAT), the provided basic Batikpattern (jpg) that is choosen by user will bedeveloped into the new patterns. The validity of this Batik patterndevelopment software are tested throughblackbox method to identify whether theapplication in this software work well or not.The finding of this research reveals thatgeometric operation in this West Borneo’sBatik pattern development software can resultnew Batik patterns with 98,89% success rate.